Knitting comes of age: the development of a scientific approach to the study of knitwork - Malcom-Davies, Jane (2019)
Knitting has received scant attention in the scientific study of textiles despite its continued popularity as a handicraft. As a result, relatively little is published about the evidence for early knitting. It is frequently the victim of mistaken identity: items made by needle binding are often described as knitted; and many more items which are knitted remain unidentified as such. A draft protocol inspired by the Centre International d’Étude des Textiles Anciens’ system for the analysis of woven textiles has been developed as part of a project to investigate Knitting in Early Modern Europe (KEME). A lack of unambiguous terminology was also identified as a challenge to the scholarly scrutiny of knitting’s origins. The evolution of a protocol and terminology and their application to a collection of knitted caps from the sixteenth century (now published online) is reported here.   Received: 2018-7-31 Revised: 2018-12-19 Accepted: 2019-1-15 Online: 2019-2-25 Publication: 2019-4-30